An Investigation into Netizen Comments on Indonesian Prominent Leaders’ Instagram Posts And Language Learning Implications - Hidayat, Didin Nuruddin; Septiawan, Yudi; Defianty, Maya; Sufyan, Agus; Eviyuliwati, Ismalianing (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2022)
Instagram serves as an example of the most famous social media platforms. Instagram, particularly for the executives, can favorably relate connections among politicians, voters, and other supportive or contending parties. The current research aimed to analyze the form of social criticism delivered by netizens on the comments towards three Indonesian politicians' Instagram posts, namely Anies Baswedan, Ridwan Kamil, and Ganjar Pranowo, who have millions of followers putting concerns towards what they did on Instagram. Besides, the research also aimed to identify some pedagogical implications of Instagram on language learning. A qualitative approach was employed to uncover the three dimensions of the discourse: positivism-empiricists, constructivism, and critical into one analysis unit or social cognition. The research found that netizens' comments were in line with the status postings of each of the governor published on Instagram, focus on the three governors' performance during their tenure, and affected by the background of the supporting parties. This research supports the idea that Instagram is a viable means of language learning because it can provide a meaningful context to learn a language.